Tantalum Nitride Nanosheets for Photoacoustic Imaging‐Guided Photothermal Cancer Therapy. (26th August 2021) - Lin, Pu; Luo, Peifu; Guo, Yating; Qiu, Honglong; Wang, Min; Huang, Guoming
Abstract: In this study, the synthesis of TaN nanosheets and their application in theranostic agents is reported. After coating polyethylene glycol (PEG) on the TaN nanosheets, the as‐synthesized PEG‐modified TaN nanosheets (TaN‐PEG) show good stability and biocompatibility. Because of their high absorbance in the near‐IR region, TaN‐PEG can be utilized as photoacoustic imaging contrast agents for tumor imaging. Moreover, TaN‐PEG has significant photothermal conversion performance, exhibiting effective laser‐induced tumor ablation capability. The TaN‐PEG possessing excellent photoacoustic contrast effect and photothermal properties thus have great promise in theranostic applications, especially imaging‐guided cancer treatment. Abstract : Polyethylene glycol (PEG)‐modified TaN nanosheets (TaN‐PEG) are synthesized and their application in theranostic agents is investigated. TaN‐PEG can generate significant photoacoustic contrast enhancement and effectively inhibit tumor growth under 808 nm laser irradiation through photothermal effects. Therefore, TaN‐PEG have great potentials in photoacoustic imaging‐guided photothermal cancer treatment.